Formal Aspects of Polyvariant Specialization - Rohde, Henning Korsholm (BRICS Report Series, 2005)
We present the first formal correctness proof of an offline polyvariant specialization algorithm for first-order recursive equations. As a corollary, we show that the specialization algorithm generates a program implementing the search phase of the Knuth-Morris- Pratt algorithm from an inefficient but binding-time-improved string matcher.